Working tobacco hands - Martínez, Lourdes Salazar (Fotocronografias, 2023)
Workers who produce tobacco form part of an industry that is characterised by various forms of inclusion and exclusion. They have little or no access to labour rights; their working hours are long, and their wages are unregulated and subject to abuse. Work is also not the same for everyone and in particular Mexican indigenous workers are trapped by the informality that characterises farm labour governed by transnational companies such as Philip Morris and British American Tobacco.